Diversity Combining Using Maxima Ratio Combining for All Modulation Mode - Yusuf Kurniawan; Andyes Fourman D.A. Sudirja (Universitas Ahmad Dahlan, 2014)
The destruction caused by channel can be seen by the existence of Amplitude and Phase Shift. By using the 6 Ways Diversity Combining method (6 Antennas/Receivers), it is expected that the disruption caused by Amplitude and Phase Shift can be suppressed as small as possible. In addition, by using diversity combining module, we will get a large SNR output which has a value sum of SNR of each diversity path. The design of Diversity combining module begins with MATLAB functional design as a big picture of the whole system. Subsequently, it will be made the hardware based on the MATLAB functional. This architectural design that will be the cornerstone in the MATLAB bit precision manufacturing. Then MATLAB bit precision will be designed as the foundation of the VHDL design. Diversity combining the output module meets the standards specified by the DVB consortium. In the hardware (FPGA) test results of diversity combining, the maximum working frequency is 44.56 MHz which has shown that is qualified with the standard sampling clock (9.142 MHz). This design also needs 4% of total FPGA Cyclone II 484I8 combinational units which is 2499 units and it needs also 3% of total register of FPGA Cyclone II 484I8 which is 1720 register units.